GAMBARAN DERAJAT NYERI PUNGGUNG BAWAH PADA IBU HAMIL TRIMESTER III DI RUMAH BERSALIN HIKMAH DESA TAMBAKAGUNG KECAMATAN PURIKABUPATEN MOJOKERTO - Saudah, Noer; Ayu Anggraini, Ria (Jurnal Keperawatan Bina Sehat, 2014)
During pregnancy, women will experience changes both of anatomy, physiology, and psycology that causes discomfort during pregnancy. One of the discomfort often experienced by pregnant women is back pain. Back pain is a disorder experienced by many pregnant women who do not only occur in a particular trimester, but can be experienced long periods of gestation until postnatal period. Woman who have had back pain before high-risk pregnancies through the same thing when pregnant, therefore it is important to be able to distinguish back pain caused by pregnancy with back pain resulting from other causes (Fraser, 2009) . The study aims to describe the degree of lower back pain in third trimester pregnant women in Rumah Bersalin Hikmah at Tambakagung village Puri subdistrict, Mojokerto district. The research design used in this research is descriptive research that describes the degree of lower back pain in third trimester pregnant women. . The number of samples to be examined were 30 respondents with a consecutive sampling method, the vast majority of third trimester pregnant women feel lower back pain in pregnancy because increased of age of gestation that make the vertebrae curve become lordosis and it cause the distress of vertebrae, most pregnant women feel lower back pain which is a physiological thing.Keywords : lower back pain, bourbanais pain scale